Contemporary Reading of Max Weber’s Ideas on the Interaction Between Cultural Factors and Economic Growth - Tanushev, Christian (Research Papers, 2018)
In globalized world, the impact of cultural differences on economic activity is becoming more and more pronounced. The subject of the study is the modern reading of Max Weber’s views on the impact of cultural factors on economic growth. The main thesis is that, both historically and in modern times, economic relations are closely intertwined with social factors and they influence each other. The research is focused on the impact of the cultural environment on: building personal qualities that directly influence the economic results, the formation of social knowledge and skills in individuals, the criteria for optimization and the distribution of goods and their application in modeling in the "game theory". Human well-being is the criterion for assessing the development of the economic system and indicators for improving the quality of life should reflect social processes.